2022
DOI: 10.1093/eurheartjsupp/suac121.026
|View full text |Cite
|
Sign up to set email alerts
|

918 Early Recognition of Subclinical Atrial Fibrillation in Patients Implanted With Different Devices

Abstract: Background Atrial fibrillation (AF) is the supra-ventricular tachyarrhythmia mostly encountered in the clinical practice.While appearing silent or with a constellation of symptoms, it confers a 5-fold risk of stroke. Early detection is mandatory to establish the diagnosis and recommend anticoagulation. Besides the arrhythmia recognition through several tools, such as Holter ECG and loop recorders, it has been underlined that cardiac implantable electronic devices with an atrial lead can help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We found one small trial with 48 participants, published as an abstract only. 13 No participants in the study had a stroke. This trial also reported that 2 patients died from gastrointestinal bleeding, and one additional patient had nonfatal major bleeding.…”
Section: Resultsmentioning
confidence: 99%
“…We found one small trial with 48 participants, published as an abstract only. 13 No participants in the study had a stroke. This trial also reported that 2 patients died from gastrointestinal bleeding, and one additional patient had nonfatal major bleeding.…”
Section: Resultsmentioning
confidence: 99%